Епістолярій остарбайтерів як джерело вивчення повсякденного життя українців на території Третього Рейху в роки Другої світової війни (на прикладі Срібнянського району Чернігівської області) - Нестеренко, Л. (Сiверянський лiтопис, 2016)
На основі листів остарбайтерів у статті охарактеризовано умови проживання та режим роботи вихідців із Срібнянського району на території Третього Рейху в період Другої світової війни. У роботі висвітлено основні теми, які було порушено українською молоддю у листах. На основе писем остарбайтеров в статье дана характеристика условий жизни и режима работы уроженцев из Сребнянского района на территории Третьего Рейха в период Второй мировой войны. В работе освещены основные темы, которые были подняты в письмах украинской молодёжью. One of the many funds of the World War II period, which are stored in the State Record Office of Chernihiv region, is a collection of letters and postcards of Soviet citizens from Nazi Germany. The letters of the Ostarbeiters, who were deported from the Chernihiv region during the Nazi occupation, were added to the fund. Letters are grouped in individual cases or in several cases according to all 39 districts, which at that time were part of the region. There are letters in two of the cases, which were sent to the localities of the Sribne district. During the Nazi occupation (September, 1941-September, 1943), 1115 people were relocated to Germany from the aforecited district, among them 482 men or 43% and 633 women or 57%. The greater part of the letters of the Sribne district Ostarbeiters (about 160) are dated August-September 1943. All letters were written on standard single or double sheets of paper. Regarding the content of the letters, all of them are different. There are letters written concerning one subject matter (the life in Germany, personal experiences). In some of the postcards, however, the prevailing information concerns soldiers’ home and reflections on life in Ukraine, while personal information is written briefly. The emotional colouring of the letters varies as well. The men mostly wrote in a brief and restrained manner, while the style of the women’s letters was exuberant, emotional, not only positive but also neutral and negative. On some of the sheets, there are visible spots or letters washed out with tears. Having analyzed the contents of the letters written by Ostarbeiters of the Sribne district, the main parts were distinguished: date of writing and date of sending or «pushchennia» , greeting relatives and friends, gratefulness for letters or concerns about their absence, some news about everyday life (work, working hours, salary, food, clothing and footwear, harvest, friends, loved ones, entertainment, correspondence with the other Ostarbeiters or friends that were at home and in Germany, personal experiences, plans to return home, nature, weather, etc.), thoughts about news from home, worries about family and farewell.